Molecular Characterization of Clinical Linezolid-Resistant Staphylococcus epidermidis in a Tertiary Care Hospital - Florian Campmann; Hauke Tönnies; Christian Böing; Franziska Schuler; Alexander Mellmann; Vera Schwierzeck (Microorganisms, 2023)
Staphylococcus epidermidis (S. epidermidis) is part of the human skin flora but can also cause nosocomial infections, such as device-associated infections, especially in vulnerable patient groups. Here, we investigated clinical isolates of linezolid-resistant S. epidermidis (LRSE) collected from blood cultures at the University Hospital Münster (UHM) during the period 2020–2022. All detected isolates were subjected to whole genome sequencing (WGS) and the relatedness of the isolates was determined using core genome multilocus sequence typing (cgMLST). The 15 LRSE isolates detected were classified as multilocus sequence type (ST) 2 carrying the staphylococcal cassette chromosome mec (SCCmec) type III. All isolates showed high-level resistance for linezolid by gradient tests. However, no isolate carried the cfr gene that is often associated with linezolid resistance. Analysis of cgMLST data sets revealed a cluster of six closely related LRSE isolates, suggesting a transmission event on a hematological/oncological ward at our hospital. Among the included patients, the majority of patients affected by LRSE infections had underlying hematological malignancies. This confirms previous observations that this patient group is particularly vulnerable to LRSE infection. Our data emphasize that the surveillance of LRSE in the hospital setting is a necessary step to prevent the spread of multidrug-resistant S. epidermidis among vulnerable patient groups, such as patients with hematological malignancies, immunosuppression or patients in intensive care units.